Mast cell activation syndrome: is anaphylaxis part of the phenotype? A systematic review. Issue 5 (October 2021) - Sabato, Vito; Michel, Moïse; Blank, Ulrich; Ebo, Didier G.; Vitte, Joana
Abstract : Purpose of review: Mast cell activation syndrome (MCAS) and anaphylaxis are the result of a spontaneous or triggered pathological degranulation of mast cells (MCs) and might have as substrate normal or pathological MCs (increased burden, aberrant MCs or both). Recent findings: This review summarizes the most recent evidence on immunoglobulin E (IgE)-mediated and non IgE-mediated mechanisms underlying MC activation and degranulation and highlights the importance of standardized diagnostic criteria for MCAS. Application of these criteria implies that in most cases the clinical presentation of MCAS meets the diagnostic criteria for anaphylaxis. Summary: Integrating clinical parameters and diagnostic test recognition and underlying clonal MC disease are of utmost importance for a patient-tailored approach. Hereditary alpha-tryptasemia can be encountered in context of anaphylaxis, MCAS and primary MC disorders.